2022
DOI: 10.1155/2022/2154577
|View full text |Cite|
|
Sign up to set email alerts
|

Construction and Management of Intelligent Campus Based on Student Privacy Protection under the Background of Artificial Intelligence and Internet of Things

Abstract: With the coming of the era of artificial intelligence development and the mobile Internet of things, privacy security will become more and more prominent. As the contemporary college students have gradually developed into one of the main forces of the next generation of network information technology and intelligent terminals of Internet mobile communication, the problem of privacy and protection of college students in the era of artificial intelligence and the Internet of Things has naturally become a practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This emphasizes the importance of incorporating ethical principles and legal regulations into AI literacy education to protect data in blended learning models. By understanding and adhering to ethical and legal guidelines, educators and students can reduce risks and protect sensitive information (Yi & Li, 2022). This study revealed a significant positive effect of Introduction to Artificial Intelligence on data security and privacy.…”
Section: Discussionmentioning
confidence: 77%
“…This emphasizes the importance of incorporating ethical principles and legal regulations into AI literacy education to protect data in blended learning models. By understanding and adhering to ethical and legal guidelines, educators and students can reduce risks and protect sensitive information (Yi & Li, 2022). This study revealed a significant positive effect of Introduction to Artificial Intelligence on data security and privacy.…”
Section: Discussionmentioning
confidence: 77%
“…Contextual inquiry, a method of ethnographic study developed by Yi and Li (2022), aims to comprehend user needs and workflows in their natural environment. By using this approach in the context of a smart campus, designers of AI-powered features can gain deep insights into users' daily experiences and create features that flow naturally into their routines.…”
Section: Human-centered Ai (Hcai)mentioning
confidence: 99%
“…With a boom charge above 50% anticipated for the subsequent market statistics declare that the worldwide market for AI schooling experienced awesome development, reaching $370 million in 2017. In step with projections, this marketplace could soar to $3.6 billion with the aid of the give-up of 2023, representing a fantastic compound annual boom price of almost 47 percent in 10 years (Yi & Li, 2022). The Asia Pacific area is well-placed to take the lead and emerge as the quickest-growing marketplace for AI education.…”
Section: Introductionmentioning
confidence: 99%